It takes a community to maintain a tree hollow: Food web complexity enhances decomposition and wood mould production. (30th July 2022) - Wetherbee, Ross; Birkemoe, Tone; Asplund, Johan; Renčo, Marek; Sverdrup‐Thygeson, Anne
Abstract: Veteran trees are keystone structures and play vital roles in ecosystems. Tree hollows, which are filled with a mix of leaves and wood that is transformed by the biotic community into wood mould, represent an important microhabitat. Tree hollow communities consist of three major groups of organisms: microbes, mesofauna (nematodes, mites and springtails) and macrofauna (beetles, millipedes and other insects). Little is known about the interplay between associated biota and their importance for decomposition and wood mould production. The aim of this study was to test how initial food web complexity in artificial tree hollows influences community structure, decomposition, and wood mould production. We used large wooden boxes to imitate natural hollows, and mounted them on 20 veteran oaks in Southern Norway. The food webs were manipulated into three levels: (i) a complex community with macrofauna and mesofauna, (ii) a simple community without macrofauna, and (iii) only the defaunated material. Three boxes (one of each treatment, N = 60 boxes) were mounted on each oak and left in the field from May 2017 to October 2019 (28 months). After the field experiment, macrofauna and mesofauna were collected and identified, mass loss in the boxes was determined, and nitrogen and phosphorus concentrations in the wood mould were measured. We found that the complex community treatment had the greatest diversity of beetles and the highest number of predatory macrofauna. The nematodes within the complex community treatment had greater trophic structuring with K‐selected species associated with stable conditions. The nematodes communities also indicated that the complex community had a balanced decomposition pathway, while the simple community was dominated by fungi and the defaunated community by bacteria. Lastly, we found that the boxes with the complex community treatment had the highest overall rate of mass loss, and greater amounts of wood mould with higher concentrations of nitrogen and phosphorus. Our results indicate that macrofauna in artificial hollows increase trophic structuring, enhance decomposition rates and wood mould production, and mediate the decomposition pathway. These findings highlight the importance of food web complexity for promoting biodiversity and ecosystem functioning in veteran tree hollows. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.